Perencanaan Teknis Operasional Pengelolaan Sampah: Studi Kasus: Kawasan Perumahan BTN Rajawali Residence Kota Kendari - Sah, Emang; Rosdiana, Rosdiana; Sakay, Ratna (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
BTN Rajawali Residence has 88 building units with type 45 (commercial), if the assumption is that each house is occupied by 5 people, 440 people will produce waste. BTN Rajawali Residence has waste problems such as the lack of available infrastructure so that many people throw garbage out of place. The purpose of this study is to identify waste generation, waste composition and analyze the existing conditions of waste management operational techniques in the housing and then plan waste management operational techniques. Sampling was carried out for eight (8) consecutive days in accordance with SNI 19-3964-1994 on methods of collection and measurement of urban waste and interviews for data collection on the existing conditions of technical waste management operations. The results of this study show that the waste generation of BTN Rajawali Residence Housing is 71.601 kg with an average of 11.934 kg/day/source which is equal to an average of 0.0850 kg/day/person. Based on the results of observations and interviews at the research location, the existing conditions of operational waste management techniques, the BTN Rajawali Resindence housing community has not implemented good waste management operational techniques according to existing regulations. Operational technical planning includes segregation, containerization, collection/transportation, processing and temporary disposal sites (TDS). The planned sorting is based on SNI 19-2454-2002 by sorting wet waste (organic), dry waste (inorganic) and residual waste by each household (from the source), referring to SNI 19-2454-2002 (procedures for urban waste management operational techniques) So, a container with a capacity of 40 liters is planned, with a barrel height of 60 cm, length 40 cm and width 40 cm. Then, it is planned for a waste transportation tool with a capacity of 200 kg of cargo, a tub height of 80 cm, a tub width of 130 cm and a length of 180 cm. The planned waste processing is composting with the individual method and the natural process with a composter barrel height of 50 cm diameter 30 cm. The TPS used to dispose of community waste is a communal TDS developed by the Government of the Environment and Forestry Service (GEFS) of Kendari City.